Apoptosis and apoptotic mimicry in Leishmania: an evolutionary perspective - El-Hani, Charbel; Borges, Valeria M.; Wanderley, João Luiz M.; Barcinski, Marcello A. (Frontiers in Cellular and Infection Microbiology, 2012)
Apoptotic death and apoptotic mimicry are defined respectively as a non-accidental death and as the mimicking of an apoptotic-cell phenotype, usually by phosphatidylserine exposure. In the case of the murine infection by Leishmania spp, apoptotic death has been described in promastigotes and apoptotic mimicry in amastigotes. In both situations they are important events of the experimental murine infection by this parasite. In the present review we discuss what features we need to consider if we want to establish if a behavior shown by Leishmania is altruistic or not: does the behavior increases the fitness of organisms other than the one showing it? Does this behavior have a cost for the actor? If we manage to show that a given behavior is costly for the actor and beneficial for the recipient of the action, we will be able to establish it as altruistic. From this perspective, we can argue that apoptotic-like death and apoptotic mimicry are both altruistic with the latter representing a weaker altruistic behavior than the former.